2022
DOI: 10.3390/ma15062052
|View full text |Cite
|
Sign up to set email alerts
|

Study of Nano h-BN Impact on Lubricating Properties of Selected Oil Mixtures

Abstract: Our experiments aimed to study the influence of layered materials with nanometric-scale particles, which are part of lubricant oils, on their tribological properties. The object of this study was a lubricant oil made using base oil PAO4, which contained nanoparticle hexagonal boron nitride (nano h-BN) and a dispersant based on succinic acid imide. Comparative tests for engine oil (CB30) were also performed. The paper presents the method of preparing the test material and the tribological test results, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…12,16 Many research findings have also indicated that nanoparticle additives are more effective than microparticle additives in improving the tribological properties of base oils because the size of nanoparticles and surface roughness are on the same scale. [17][18][19] Urbaniak et al 20 believed that h-BN nanoparticles created a superior protective film that can significantly prevent friction and promote wear resistance. Kumar et al 21 investigated the tribological performance of lithium complex grease with additives of h-BN micro-, submicro-, and nanoparticles and found that nanoparticles of h-BN exhibited the best antifriction and anti-wear properties.…”
Section: Introductionmentioning
confidence: 99%
“…12,16 Many research findings have also indicated that nanoparticle additives are more effective than microparticle additives in improving the tribological properties of base oils because the size of nanoparticles and surface roughness are on the same scale. [17][18][19] Urbaniak et al 20 believed that h-BN nanoparticles created a superior protective film that can significantly prevent friction and promote wear resistance. Kumar et al 21 investigated the tribological performance of lithium complex grease with additives of h-BN micro-, submicro-, and nanoparticles and found that nanoparticles of h-BN exhibited the best antifriction and anti-wear properties.…”
Section: Introductionmentioning
confidence: 99%
“…Due to good mechanical, lubricating and oxidation resistance, it is expected to become one of the top choices for green lubricating oil additives after reasonable development [15]. Over the past few decades, plenty of studies on h-BN as a lubricating additive have been reported [2,[16][17][18][19][20][21][22]. Yang et al [2] found that as a friction additive in mineral oil, the as-prepared lipophilic BN nanosheets can reduce the coefficient of friction (COF) by 20.2%.…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, the track of the wear scar becomes significantly shallower. Urbaniak et al [19] studied the tribological properties of BN as an additive to PAO4 base oil. They found that adding the h-BN layered nanomaterial to the lubricating oil can be a good solution for obtaining a lubricating oil with a ~27% greater galling load than the base oil.…”
Section: Introductionmentioning
confidence: 99%